Entrepreneurial intention among female university students in Oman - Echchabi, Abdelghani; Omar, Mohammed Mispah Said; Ayedh, Abdullah Mohammed (Inderscience Enterprises Ltd, 2024)
The aim of the study is to identify the factors that influence the entrepreneurial intention among female students in Oman. The study used a survey questionnaire to collect data for a sample of 384 respondents in Oman. The study ensured that the major country regions and universities are covered. The collected data was analysed using partial least squares (PLS) method as well as basic descriptive statistics. The findings revealed that perceived behavioural control and personal attitude were the main factors that influence Omani female students' entrepreneurial intention. Attitude to risk, facilitating conditions and subjective norm were found to have no significant impact on entrepreneurial intention. The focus on female entrepreneurship is both timely and necessary worldwide and particularly in Oman. The findings have significant theoretical and practical implications that would certainly improve the entrepreneurship activities among female undergraduate students in Oman.